2023
DOI: 10.1097/prs.0000000000010530
|View full text |Cite
|
Sign up to set email alerts
|

Improved Facial and Skull-base Symmetry Following Osteotomy and Distraction of Unilateral Coronal Synostosis

Abstract: Unilateral coronal synostosis (UCS) constitutes approximately 10% of all incidents of craniosynostosis and primarily causes ipsilateral retrusion and contralateral bulging of the forehead. 1 In addition, UCS can lead to complex secondary deformities that comprise facial asymmetries with deviation of the nose toward the affected side, orbit dystopia, zygomatic asymmetries, and possible effects involving dental occlusion. [2][3][4][5][6][7] The functional consequences of UCS can include strabismus, amblyopia, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The use of linear measurements in combination with GM and asymmetry analyses could potentially offer a more comprehensive view of ULS and the restorative impact of SAS. Another form of DO is the use of a distractor device, which requires manual manipulation and has successfully treated unicoronal synostosis 37 . However, a study comparing this method of DO to CVR when treating ULS demonstrated no significant differences regarding perioperative bleeding, operation time, or 90-day postoperative complications 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The use of linear measurements in combination with GM and asymmetry analyses could potentially offer a more comprehensive view of ULS and the restorative impact of SAS. Another form of DO is the use of a distractor device, which requires manual manipulation and has successfully treated unicoronal synostosis 37 . However, a study comparing this method of DO to CVR when treating ULS demonstrated no significant differences regarding perioperative bleeding, operation time, or 90-day postoperative complications 38 .…”
Section: Discussionmentioning
confidence: 99%
“…I n this study, Mellgren et al retrospectively evaluated 14 patients with isolated unilateral coronal synostosis (UCS) treated with fronto-orbital distraction (FOD). 1 They report operative details, including blood loss and length of stay, postoperative complications, and morphologic changes by comparing preoperative and end-consolidation computed tomographic imaging. Their data suggest improvements in orbital and anterior cranial base morphology following FOD.…”
mentioning
confidence: 99%